Molecular Alterations in the Hippocampus after Experimental Subarachnoid Hemorrhage. Issue 1 (January 2014) - Han, Sang Myung; Wan, Hoyee; Kudo, Gen; Foltz, Warren D; Vines, Douglass C; Green, David E; Zoerle, Tommaso; Tariq, Asma; Brathwaite, Shakira; D'Abbondanza, Josephine; Ai, Jinglu; Macdonald, R Loch
Patients with aneurysmal subarachnoid hemorrhage (SAH) frequently have deficits in learning and memory that may or may not be associated with detectable brain lesions. We examined mediators of long-term potentiation after SAH in rats to determine what processes might be involved. There was a reduction in synapses in the dendritic layer of the CA1 region on transmission electron microscopy as well as reduced colocalization of microtubule-associated protein 2 (MAP2) and synaptophysin. Immunohistochemistry showed reduced staining for GluR1 and calmodulin kinase 2 and increased staining for GluR2. Myelin basic protein staining was decreased as well. There was no detectable neuronal injury by Fluoro-Jade B, TUNEL, or activated caspase-3 staining. Vasospasm of the large arteries of the circle of Willis was mild to moderate in severity. Nitric oxide was increased and superoxide anion radical was decreased in hippocampal tissue. Cerebral blood flow, measured by magnetic resonance imaging, and cerebral glucose metabolism, measured by positron emission tomography, were no different in SAH compared with control groups. The results suggest that the etiology of loss of LTP after SAH is not cerebral ischemia but may be mediated by effects of subarachnoid blood such as oxidative stress and inflammation.